A cross-cultural analysis of celebrity practice in microblogging. (24th July 2018) - Zhang, Min; Wu, Doreen
Abstract : This study attempts to explore how celebrities manage rapport with followers through an array of speech acts in microblogging - the essential building blocks of virtual identity on social media. Six months of postings of eight of the most-followed Twitter and Weibo celebrities from USA and China were retrieved and analysed. A taxonomy of nine speech acts for rapport management was identified to give a categorised descriptive snapshot of celebrities' microblogging discourse.The results revealed that the celebrities from both countries employ self-disclosing speech acts extensively to report events, anecdotes, or initiate small talk with fans for solidarity building. In addition, the attention fostered by the personalised, affective, and eye-catching self-disclosure posts is frequently directed to the posts promoting their professional activities or products to commercialise the solidarity as much needed for maintaining a strong fan base. In general, the celebrity practices in USA and China display a converging trend as the prevalent speech acts are largely overlapping across cultures, while culture-specific microblogging behaviours were also identified from the less frequently performed speech acts.